Analysis of the Feasibility Level of the Moodle Integrated WordPress-Based Chemistry Learning Website to Improve Student Learning Outcomes on the Elements Periodic System Material - Nur Huda; Kholifatur Rosyidah; Faiz Rizky Nur Awwaludin; Kusumawati Dwiningsih (Universitas Lampung, 2021)
This study aims to determine the feasibility of a WordPress-based integrated chemistry learning website Moodle to improve student learning outcomes on the material of the periodic system of elements seen from content and construct validity. The type of research used is Research and Development (RD) with a 4D development model, namely Define, Design, Develop and Disseminate. In this study, the development model is limited to the development stage. This research was conducted using a learning website review sheet instrument and a learning website validation sheet divided into a content validity sheet and a construct validity sheet. The results of expert validation, data obtained if the average percentage of content and construct conformity is 89.59% and 86.67%, respectively, in the very valid category. Based on these results, the chemistry learning website generated from this research is valid and feasible to use as a learning medium.Keywords: Learning website, WordPress, Moodle, learning outcomes. DOI: 10.23960/jppk.v10.i3.2021.04